OTAi Burger Ordering Management Application - PANIR SELWAM, NAGULAN; Mohd. Yasin, Suhaila (Applied Information Technology And Computer Science, 2025)
The OTAi Burger Ordering Management Application modernizes smaller burger stalls like OTAi Burger in Puncak Alam, Selangor. Key challenges included price discrepancies, high staff turnover, and inefficient manual ordering. The Prototyping Model ensures user feedback refines each iteration. Built with React Native for cross-platform development and Firebase for secure data management, the application automates orders, standardizes pricing, provides detailed receipts, and offers modules for menu, sales analytics, feedback, job vacancies, and staff management. By reducing reliance on third-party services, it boosts efficiency, transparency, and customer satisfaction. This solution helps smaller food businesses improve performance and customer loyalty in a competitive market.